Mobile Classroom for Military Tactical Training in Cavalry Mission Planning - Rojas-Ballesteros, Daniel Eduardo; Molina Saldarriaga, César Augusto; Palomo Navarro, Cristie (Ingeniería Solidaria, 2019)
Introduction: This article is the result of the research project entitled “Mobile classroom for military tactical training in cavalry mission planning, development in the Cavalry school of the Colombian Army from 2010 to 2017”. Its purpose is to identify tools to improve the training process of military personnel.Problem: The training is carried out in a theoretical environment as there is currently no alternative means to training personnel in this field. The present investigation aims to improve the instruction of the army personal with their varying roles and ranks –officers, non-commissioned officers (NCOs) and enlisted soldiers–, when encountering individual and collective training.Objective: Evaluate the impact of the implementation of a mobile classroom equipped with simulation tools, as a strategy for the formation of the members of the Cavalry School.Methodology: Empirical study developed in 5 stages: (i) initial instruction, (ii) diagnostic test, (iii) diagnostic feedback, (iv) performance test and (v) performance evaluation. For this, the adaptation of a trailer, such as a mobile classroom, and the ARMA 3 game was used.Results: The use of the mobile classroom allowed for an increase in the number of trained people whilst reduced training times resulting in lower operating costs and greater sustainability.Conclusion: The implementation of the mobile classroom and the simulation system contributed to the development of skills and abilities, improved decision-making capacities, increased perceptual variation and improved coordination, communication and team decision-making.Originality: First mobile classroom for military training, with invention patent, 10-61804.Limitation: The investigation was carried out at the Cavalry School. The results can only be replicable in other military study centers.
Keywords: training; instruction; doctrine; simulation; military tactical y cavalry